(untitled) (Вісник: Міжнародні відносини, 2021)
The purpose of the paper is to summarize and present the fundamental trends of the last decade related to climate change, as well as interstate and global economic campaigns aimed at slowing down this process, that create a powerful new determinant for multinational enterprises (MNE) in the areas of corporate governance, risk management and sound management of climate risks and opportunities. The analysis is based on the recent studies of the leading international researchers such as International Energy Agency and The Economist Intelligence Unit, dedicated United Nations bodies, Universities, and also association of MNE Task Force on Climate-related Financial Disclosures. Results of the analysis showed that climate risks and opportunities already have a clear monetary expression and impact on MNE. Modern efficient business faces a need to build an effective system for managing such risks, which, in addition to the direct effect on MNE, will also be an important signal for the stakeholders, that in turn may reduce the cost of the raised capital and increase the level of revenues. For some EU countries, it will soon become mandatory to cover climate risk management principles and approaches in their annual reports. Internal models are being developed that show the impact of climate change on MNE business (for example, an increase in total temperature by 1,5 °C, 2 °C, 4 °C). Therefore, a unified approach towards climate risk management becomes a topic of high importance for MNE and its stakeholders, including regulators, investors, shareholders and society. The conducted analysis provides deep understanding of the main drivers of climate risk management for MNE together with its practical implication that is emerging in the world economy.